PENGARUH MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) BERBANTUAN LITERACY CLOUD TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS 1 - Nuraini, Kalila; Nur Yasin, Fajar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of the Numbered Head Together (NHT) learning model assisted by Literacy Cloud on the early reading skills of first-grade students in Indonesian language subjects at SDN Ganting. The research employed a quantitative approach using a Quasi-Experimental Design. The subjects consisted of 22 students from class II A as the pilot group, 26 students from class I B as the experimental group, 27 students from class I A as the control group, and the classroom teacher as the facilitator. Based on the results obtained at SDN Ganting through an independent sample t-test, the significance value (2-tailed) was 0.000, which is less than 0.05, and the calculated t-value (5.115) was greater than the critical t-value (1.675) at the 5% significance level. These findings indicate that the NHT learning model assisted by Literacy Cloud has a significant impact on students’ early reading skills in Indonesian language learning. Therefore, this study supports the enhancement of students’ early reading abilities through a fun and interactive learning environment.